1995
DOI: 10.1152/jn.1995.73.2.810
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of selective long-term potentiation of excitatory synapses in stratum oriens/alveus interneurons of rat hippocampal slices

Abstract: 1. We investigated long-term potentiation (LTP) of synaptic transmission in different populations of interneurons in the CA1 region of rat hippocampal slices using whole cell recordings. We elicited excitatory postsynaptic currents (EPSCs) in interneurons located in stratum oriens near the alveus (O/A) or in stratum lacunosum-moleculare near the stratum radiatum border (L-M) by electrical stimulation of nearby axons in stratum oriens and radiatum, respectively. 2. High-frequency stimulation (100 Hz, 1 s) of ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 0 publications
3
76
1
Order By: Relevance
“…Alternatively, we would favor the lack of some of the necessary components required for LTP induction. Our results contrast to those reported by Ouardouz and Lacaille (1995), who reported LTP in an unidentified st. oriens cell type. In these studies, tetanic stimulation was used to induce LTP, which does not allow a clear distinction between direct plasticity and passive propagation.…”
Section: Discussion Ltp In Oaiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Alternatively, we would favor the lack of some of the necessary components required for LTP induction. Our results contrast to those reported by Ouardouz and Lacaille (1995), who reported LTP in an unidentified st. oriens cell type. In these studies, tetanic stimulation was used to induce LTP, which does not allow a clear distinction between direct plasticity and passive propagation.…”
Section: Discussion Ltp In Oaiscontrasting
confidence: 99%
“…Therefore, the possibility of additional synaptic plasticity occurring in nonpyramidal cells would greatly increase both the power and the level of complexity of signal processing in the CA1 subfield. Indeed, several reports have shown that after tetanic stimulation, changes occur in (1) evoked nonpyramidal cell firing probability (Buzsaki and Eidelberg, 1982), (2) IPSP amplitudes recorded on pyramidal cells (Xie and Sastry, 1991; Morishita and Sastry, 1991), and (3) EPSP or EPSC amplitudes recorded in interneurons (Taube and Schwartzkroin, 1987;Stelzer et al, 1994;Ouardouz and Lacaille, 1995). In addition, however, synaptic depression occurring at the Schaffer collateral-pyramidal neuron synapses can "passively propagate" to interneurons of the st. oriens/alveus and influence the excitatory drive of these cells (Maccaferri and McBain, 1995).…”
mentioning
confidence: 99%
“…To examine whether LTP was a property of excitatory synapses specific to certain types of interneurons, the paradigm of TBS paired with depolarization was applied to interneurons in R͞LM (12,14) and to pyramidal cells. In addition, this series of experiments was conducted in ACSF containing normal (2 mM) Ca 2ϩ ͞Mg 2ϩ levels to verify that LTP was not inducible solely in elevated extracellular Ca 2ϩ ͞Mg 2ϩ levels.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling studies suggest that plasticity at interneuron synapses is important for learning and recall by hippocampal neuronal networks (9). However, experimental evidence of long-term synaptic plasticity at input and͞or output synapses of hippocampal interneurons has been controversial (10)(11)(12)(13)(14)(15)(16). This uncertainty has been due, in part, to the heterogeneity of interneuron types present in the hippocampus and to the complexity of the network (6,17,18).…”
mentioning
confidence: 99%
“…These properties depend on receptor subunit composition (particularly the relative absence of GluR-B in interneurones and perhaps on the relative presence of GluR_D) and are regulated by posttranslational alternative splicing and RNA editing (Bochet et al 1994;Geiger et al 1995). We suggest that the functional reliability of the e i connection (which can even allow unitary EPSPs to elicit action potentials (Knowles & Schwartzkroin, 1981;Lacaille et al 1987;Miles, 1990)) takes on biological meaning because of the role interneurones play in high-frequency cortical oscillations, with the apparent necessity for interneurone doublets to occur during long-range synchrony of firing, and that usedependent increases in efficacy of excitatory synapses on interneurones (Taube & Schwartzkroin, 1987;Ouardouz & Lacaille, 1995) may be important for the same reason.…”
Section: Ampa Receptors On Interneuronesmentioning
confidence: 94%